2021
DOI: 10.1126/science.abf9277
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of meningeal B cells reveals a lymphopoietic niche at the CNS borders

Abstract: The meninges contain adaptive immune cells that provide immunosurveillance of the CNS. These cells are thought to derive from the systemic circulation. Through single-cell analyses, confocal imaging, bone marrow chimeras, and parabiosis experiments, we show that meningeal B cells derive locally from the calvaria, which harbors a bone marrow niche for hematopoiesis. B cells reach the meninges from the calvaria through specialized vascular connections. This calvarial–meningeal path of B cell development may prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
376
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(393 citation statements)
references
References 51 publications
14
376
2
1
Order By: Relevance
“…S10C) but lacked Aicda, which is associated with the activation of mature B cells and germinal centre formation. Others have recently presented similar data from the spinal cord and brain meninges of adult mice, and they suggested that the CNS may act as a lymphopoietic niche (Brioschi et al 2021;Cohen et al 2021). The fact that we found proliferating B cells in early neonatal mouse meninges support this notion.…”
Section: Neutrophils Ilcs T Cells and B Cells Are A Minor Fraction Of The Resident Meningeal Leukocytes In Neonatal Micesupporting
confidence: 88%
“…S10C) but lacked Aicda, which is associated with the activation of mature B cells and germinal centre formation. Others have recently presented similar data from the spinal cord and brain meninges of adult mice, and they suggested that the CNS may act as a lymphopoietic niche (Brioschi et al 2021;Cohen et al 2021). The fact that we found proliferating B cells in early neonatal mouse meninges support this notion.…”
Section: Neutrophils Ilcs T Cells and B Cells Are A Minor Fraction Of The Resident Meningeal Leukocytes In Neonatal Micesupporting
confidence: 88%
“…Additionally, it has recently been reported that the majority of myeloid cells in the meninges are derived from the skull bone marrow both in homeostatic and pathological states (72). Of note as well is the role of the skull bone marrow as a source of B cells to the meninges, with these developing B cells travelling via the direct vascular network to the meninges to complete their maturation (73). It is worth noting however that the role of B cells in AD pathogenesis still remains elusive.…”
Section: Meninges Choroid Plexus and Skull Bone Marrowmentioning
confidence: 99%
“…Moreover, when capacity for testing is limited early in an epidemic, as with COVID-19, it can be targeted towards regions, populations, and settings most likely to have high community spread when social contact patterns are known, facilitating identification of both mildly symptomatic and asymptomatic carriers and preventing transmission by super-spreaders. When vaccines become available, a lack of accurate information impacts optimal vaccine distribution as well as vaccination booster schedules [ 14 ]. In order to fill this information gap, we describe and quantify US social contact patterns using data from the Bureau of Labor Statistics’ American Time Use Survey (ATUS), 2003–2018.…”
Section: Introductionmentioning
confidence: 99%